Analysis of potential materials for local production of a rail car component using additive manufacturing. Issue 5 (May 2022) - Muvunzi, Rumbidzai; Mpofu, Khumbulani; Daniyan, Ilesanmi; Fameso, Festus
Abstract: In the rail industry, unavailability of spare parts can have negative implications such as downtime and financial losses. Long lead times can be experienced in the process of replacing a damaged spare part. Some of the parts are expensive to produce in-house using conventional methods because of the tooling costs. It can be time consuming to wait for suppliers to replace the part if it is not produced locally. Proper maintenance of vehicles requires spare parts to be available timeously. It is necessary to investigate how parts can be produced using locally available technologies and materials. The aim of this study is to analyse potential materials that can be used to produce a rail car component. The use of Additive Manufacturing (AM) to produce parts on demand is a quicker and flexible approach when compared to conventional manufacturing methods. Taking advantage of the flexibility offered by the AM, three alternative high performance materials are considered to reduce the weight, improve functional performance and service life of the part. The performance of all the three materials are tested and analysed using Finite Element Analysis. The results of this study are useful in providing guidance on the development of a suitable process chain for producing the part locally. This demonstrates the capability of AM as a suitable approach for enabling local sustainable production of spare parts for the rail industry. Abstract : Selection; Materials; Manufacturing; Case study; Traction link; Additive manufacturing; Design; Process chain; stress; Thermal.